KONSEP PENDIDIKAN DEWI SARTIKA DAN RELEVANSINYA DENGAN PENDIDIKAN NASIONAL - Yeni Sulistiani, - (2021)
This study aims to produce a description of the concept of education according to Dewi Sartika and its relevance to National Education. Dewi Sartika is a pioneer figure in education for women. The research method used is library research. The main source of this research is Boekoe Kaoetamaan Istri and other supporting books related to Dewi Sartika. The results of the research include the definition of education, the formulation of educational objectives, the nature of educators, the nature of students, the content of education, the tools and the educational situation. According to Dewi Sartika, education is a knowledge or tool to organize, change, and advance all matters in a better direction, including students. The formulation of Dewi Sartika's educational goals was to create the nu generation that could be breathed. Educators must have compassion, be in tune with words and behavior and know manners because a teacher is an example. Students are children that are expected by Cageur, Bageur, Cepet, and Bener. The educational content provided to students includes character and religion education, language, numeracy, art, and skills. The educational tools used are counseling and example. There is a relevance between Dewi Sartika's education concept and the National Education System both in terms of the meaning of education, educational goals, the nature of educators, the nature of students, and the content of education. The useful results of this research can be used as a basis for understanding how the concept of education in Dewi Sartika's thought as well as material for further research development for educational praxis.